Keputusan Belanja Online: Dampak Social Proof, Harga dan Minat Beli - Irma Christiana; Gantara Abi Mayu Lubis; Linzzy Pratami Putri (Universitas Muhammadiyah Palembang, 2025)
Purpose – The purpose of this study was to determine and analyze the effect of social proof and price on purchasing decisions with purchase intention as an intervening variable. Design/methodology – This study uses a descriptive quantitative approach. The population in this study were active students at universities with superior and excellent accreditation in Medan, namely UMSU, USU, UNIMED who used Shopee. Sample withdrawal using purposive sampling method. To determine the achievement of the sample size using the Leme show formula, while the data analysis technique uses the Path Analysis Model Statistics, namely the Partial Least Square-Structural Equation Model (SEM-PLS) using the Smart PLS 3 application. Findings - The results of hypothesis testing show that social proof has no effect on purchase intention or on purchasing decisions. Meanwhile, price has an effect on buying interest but has no effect on purchasing decisions. In addition, buying interest is able to mediate the influence of social proof and price on purchasing decisions